ANALISIS KEBUTUHAN PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS FLIPBOOK DALAM PELATIHAN JARAK JAUH PERPAJAKAN UNTUK PEGAWAI PUSAT PEMBINAAN PROFESI KEUANGAN (PPPK) - Dika Arifiani (Jurnal Kiprah Pendidikan, 2022)
The right learning media will have an impact in encouraging the learning process. Therefore, the learning media used must be in line with the learning objectives. This study explores information about the use of learning media, data on learning difficulties, subject that become learning difficulties, as well as about the use and suitability of flipbook media in overcoming learning difficulties for participants in the Pelatihan Jarak Jauh Perpajakan Untuk Pegawai Pusat Pembinaan Profesi Keuangan (PPPK). The results of the study stated that learning media had been utilized by both participants and teachers, participants experienced learning difficulties, especially for Pajak Penghasilan. To overcome these difficulties, the teacher adds/changes the learning media, and flipbook media is appropriate to overcome the learning difficulties of the participants